2013
DOI: 10.1371/journal.pone.0062465
|View full text |Cite
|
Sign up to set email alerts
|

Mannose-Binding Lectin Blunts Macrophage Polarization and Ameliorates Lupus Nephritis

Abstract: BackgroundDeficiency in clearance of self nuclear antigens, including DNA, is the hallmark of systemic lupus erythematosus (SLE), a chronic autoimmnue disease characterized by the production of various autoantibodies, immune complex deposition and severe organ damage. Our previous studies revealed that administration of syngeneic BALB/c mice with activated lymphocyte-derived DNA (ALD-DNA) could induce SLE disease. Mannose-binding lectin (MBL), a secreted pattern recognition receptor with binding activity to DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 53 publications
3
18
0
1
Order By: Relevance
“…In the present study, we investigated the signaling pathway and found that the phosphorylations of JNK, ERK and p38 were all significantly increased in MBL –/– mice after APAP treatment, suggesting that MBL attenuates the hepatic activation of MAPKs pathway in the context of APAP overdosing. The result is consistent with our and others’ previous reports showing that MBL could significantly down‐regulate the phosphorylation of MAPKs in different cell types in response to various stimulation . Among the MAPKs, JNK acts as a central player in the pathophysiology of APAP‐induced liver injury .…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we investigated the signaling pathway and found that the phosphorylations of JNK, ERK and p38 were all significantly increased in MBL –/– mice after APAP treatment, suggesting that MBL attenuates the hepatic activation of MAPKs pathway in the context of APAP overdosing. The result is consistent with our and others’ previous reports showing that MBL could significantly down‐regulate the phosphorylation of MAPKs in different cell types in response to various stimulation . Among the MAPKs, JNK acts as a central player in the pathophysiology of APAP‐induced liver injury .…”
Section: Discussionsupporting
confidence: 93%
“…IL‐6 is highly expressed in M1 and M2b macrophages but not in M2a and M2c . Growing data show that in combination with other markers (IL‐10, LIGHT, CCL1, or/and TNF‐α), IL‐6 can identify M2b from the other macrophage subsets …”
Section: Phenotypic Markers Of M2bmentioning
confidence: 99%
“…In lupus nephritis (LN), activated lymphocyte‐derived DNA (ALD‐DNA) induces the macrophage activation and M2b polarization by activating the NF‐κB and the IRF3 signaling pathways via calcium signaling . Moreover, the activation of NF‐κB as well as MAPK signaling in macrophages is inhibited by mannose‐binding lectin (MBL), a recognition receptor with binding activity to DNA, resulting in a decrease in M2b macrophage polarization . Furthermore, ALD‐DNA‐induced M2b polarization is dependent on the acceleration of NF‐κB p50 translocation into the nucleus mediated by the PI3K and MAPK pathways .…”
Section: Modulation Of M2b Macrophage Polarizationmentioning
confidence: 99%
See 2 more Smart Citations